(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article deals with the importance of the words and word formation in a vocabulary and language, the definition of them by broad variety of foreign linguists, the utilizing of them in periods of time and various forms in verbal system. This paper provides detailed suggestions with illustrations, background of previous researches, foundations, results of them and so on. The authors and researchers with all level may use in practical and theoretical researches with the help of data in the article.